2020
DOI: 10.1017/s0007114520003347
|View full text |Cite
|
Sign up to set email alerts
|

The association between maternal fat-soluble vitamin concentrations during pregnancy and infant birth weight in China

Abstract: Fat-soluble vitamins during pregnancy are of vital importance for fetal growth and development. The present study aimed at exploring the association between vitamin A, E and D status during pregnancy and birth weight. A total of 19,640 women with singleton deliveries from a retrospective study were included. Data were collected by the hospital electronic information system. Maternal serum vitamin A, E and D concentrations were measured during pregnancy. Logistic regression was performed to estimate the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Diet was assessed using a 24 h recall and a 3-day food record [71]. This is in accordance with a recent large prospective study showing that maternal serum vitamin A concentrations during pregnancy were positively associated with LBW, and negatively associated with macrosomia [72]. Conversely, a recent systematic review and meta-analysis of 17 trials reported that vitamin A or beta-carotene levels during pregnancy did not have a significant overall effect on birthweight indicators, preterm birth, stillbirth, miscarriage or fetal loss [73].…”
Section: Discussionsupporting
confidence: 72%
“…Diet was assessed using a 24 h recall and a 3-day food record [71]. This is in accordance with a recent large prospective study showing that maternal serum vitamin A concentrations during pregnancy were positively associated with LBW, and negatively associated with macrosomia [72]. Conversely, a recent systematic review and meta-analysis of 17 trials reported that vitamin A or beta-carotene levels during pregnancy did not have a significant overall effect on birthweight indicators, preterm birth, stillbirth, miscarriage or fetal loss [73].…”
Section: Discussionsupporting
confidence: 72%
“…The meta-analysis was a secondary analysis primarily based on RCTs. Neonatal outcomes involved in exploring the effects of maternal vitamin D deficiency on offspring, including small-for-gestational-age ( 40 ), neonatal bone mass ( 41 ), infant glucose metabolism ( 42 ), infant atopic dermatitis ( 43 ), infant acute respiratory infections ( 37 ), infant birth weight ( 44 ), offspring sex ratio ( 45 ), infant gut microbiota ( 46 ), offspring socioemotional development ( 47 ), infant neurodevelopment ( 48 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the limited number of studies that have assessed the relationship of VDD and neonatal growth to date, findings have been mixed [ 22 , 24 , 67 ] and significant associations have been shown to vary by pregnancy trimester. For example, in a study of pregnant women in Spain ( n = 2358), maternal vitamin D was measured at 13–15 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency (defined as 25(OH)D < 20 ng/ml or < 69 nmol/L) was evident in 19.6% of women and was shown to predict fetal overweight (fetal weight ≥ 90 th percentile) and abdominal adiposity (abdominal circumference ≥ 90 th percentile) at birth [ 31 ]. In a separate study of Chinese women who had vitamin D assessed during the second ( n = 11,634) and third trimester of pregnancy ( n = 6609), median 25(OH)D concentration was found to be ~ 66 nmol/L, an maternal vitamin D in the third but not second trimester was negatively associated with macrosomia but not with birthweight, after adjustment for multiple confounders [ 67 ]. Variation in assessment timepoints of vitamin D during pregnancy, difference in the techniques used to analyse 25(OH)D, variation in cut points used to define VDD or variation in adjustment for critical confounders such as season of sample collection likely explain the observed inconsistent results across studies.…”
Section: Discussionmentioning
confidence: 99%